Unleashing Creativity in the Workplace: Exploring the Power of Career Commitment, Person-Job Fit, Person-Organizational Fit, and Psychological Safety in the Vibrant Nepalese Service Sector - Rijal, Rheet (Nepalese Journal of Management Science and Research, 2024)
This study investigates the role of career commitment as a mediator between person-job fit, person-organization fit, and employee creativity in Nepal's service sector. Using a positivist approach and deductive reasoning, it employs a causal-comparative method with a sample size of 439 staff. Data collection involves structured survey questionnaires, and analysis includes descriptive statistics and structural equation modeling with SPSS 20 and AMOS 22. Findings reveal that person-job fit positively influences creativity, while person-organization fit's impact is negative and insignificant. Both fits positively affect career commitment, which in turn positively influences creativity. Interaction between person-job fit and psychological safety negatively affects creativity, whereas the interaction with person-organization fit is positive but insignificant. Career commitment mediates the relationship between both fits and employee creativity. This research contributes valuable insights for enhancing creativity among employees in Nepal's service sector, offering guidance for organizations and policymakers.